Sobre la posibilidad de un conocimiento autónomo de la educación y su aplicación a finalidades educativas - Gil Cantero, Fernando (Teoría de la Educación. Revista Interuniversitaria, 2009)
The aim of this paper is to analyce the posibility of an autonomous knowledge of education as a epistemological differenciating criterion in pedagogy. The problem arises when deffending such an autonomous knowledge involves the rejection of other ways of understanding education because they do not promote that autonomy. The mistake lies in identifying epistemological differenciating criterions with what is valuable in order to educate. This work try to show that the understanding or the theory of Education as philosophical theories provides a valuable knowledge to education, as well as that knowledge is necessary in order to reach the autonomy above mentioned. It occurs the same with the understanding of the theory of education as applied theories. Each case is analyzed through the knowledge of the educational aims.